Gene-specific DNA methylation may mediate atypical antipsychotic-induced insulin resistance - Burghardt, Kyle J; Goodrich, Jacyln M; Dolinoy, Dana C; Ellingrod, Vicki L (Bipolar disorders, 2016)
Objectives Atypical antipsychotics (AAPs) carry a significant risk of cardiometabolic side effects, including insulin resistance. It is thought that the insulin resistance resulting from the use of AAPs may be associated with changes in DNA methylation. We aimed to identify and validate a candidate gene associated with AAP‐induced insulin resistance by using a multi‐step approach that included an epigenome‐wide association study (EWAS) and validation with site‐specific methylation and metabolomics data. Methods Subjects with bipolar disorder treated with AAPs or lithium monotherapy were recruited for a cross‐sectional visit to analyze peripheral blood DNA methylation and insulin resistance. Epigenome‐wide DNA methylation was analyzed in a discovery sample (n = 48) using the Illumina 450K BeadChip. Validation analyses of the epigenome‐wide findings occurred in a separate sample (n = 72) using site‐specific methylation with pyrosequencing and untargeted metabolomics data. Regression analyses were conducted controlling for known confounders in all analyses and a mediation analysis was performed to investigate if AAP‐induced insulin resistance occurs through changes in DNA methylation. Results A differentially methylated probe associated with insulin resistance was discovered and validated in the fatty acyl CoA reductase 2 (FAR2) gene of chromosome 12. Functional associations of this DNA methylation site with untargeted phospholipid‐related metabolites were also detected. Our results identified a mediating effect of this FAR2 methylation site on AAP‐induced insulin resistance. Conclusions Going forward, prospective, longitudinal studies assessing comprehensive changes in FAR2 DNA methylation, expression, and lipid metabolism before and after AAP treatment are required to assess its potential role in the development of insulin resistance.